Outcomes in Eyes with Retinal Angiomatous Proliferation in the Comparison of Age-related Macular Degeneration Treatments Trials (CATT) - Daniel, Ebenezer (Ophthalmology, 2015)
OBJECTIVE: To compare baseline characteristics, visual acuity (VA) and morphological outcomes between eyes with retinal angiomatous proliferation (RAP) and all other eyes among patients with neovascular age-related macular degeneration (NVAMD) treated with anti-vascular endothelial growth factor (anti-VEGF) drugs. DESIGN: Prospective cohort study within the Comparison of AMD Treatments Trials (CATT). PARTICIPANTS: Patients with NVAMD METHODS: Reading Center staff evaluated baseline and follow-up digital color fundus photographs (CFP), fluorescein angiograms (FA), and optical coherence tomograms (OCT) of eyes having NVAMD treated with either ranibizumab or bevacizumab over a 2-year period. RAP was identified by the intense intra-retinal leakage of fluorescein in combination with other associated features. MAIN OUTCOME MEASURES: VA, fluorescein leakage, scar, geographic atrophy (GA) on FA and retinal thickness, fluid and subretinal hyperreflective material (SHRM) on OCT, and number of intravitreal anti-VEGF injections at 1 and 2 years. RESULTS: RAP was present in 126 of 1183 (10.7%) study eyes at baseline. Mean VA improvement from baseline was greater (10.6 vs 6.9 letters; p=0.01) at one year but similar at 2 years (7.8 vs 6.2; p=0.34). At 1 year, eyes with RAP were more likely to have: no fluid (46 vs 26%; p<0.001) on OCT, no leakage on FA (61 vs 50%; p=0.03), and greater reduction in foveal thickness (-240 vs -161u, p<0.001). They were more likely to develop GA (24 vs 15%; p=0.01), and less likely to develop scar (17 vs 36%; p<0.001), or SHRM (36 vs 48%; p=0.01). These results were similar at 2 years. The mean change in lesion size at 1 year differed (-0.27 vs 0.27 DA; p=0.02) but was similar at 2 years (0.49 vs 0.79; p=0.26). Among eyes treated PRN, eyes with RAP received a lower mean number of injections in year 1 (6.1 vs 7.4; p=0.003) and year 2 (5.4 vs 6.6; p=0.025). CONCLUSIONS: At both 1 and 2 years after initiation of anti-VEGF treatment in CATT, eyes with RAP were less likely to have fluid, FA leakage, scar, and SHRM and more likely to have GA than eyes without RAP. Mean improvement in VA was similar at 2 years.